Texture profile analysis of Sonaka and Thompson seedless raisins - A, Vijaykumar; Naik, Vishal V (Journal of Postharvest Technology, 2018)
Texture Profile Analysis (TPA) is a well developed and reliable method for measuring firmness of fruits and dehydrated products. In the present investigation, an attempt has been made to study texture profile of raisins of Sonaka and Thompson seedless treated with MgCO3, K2CO3, CaCO3 and Sulphur and coated with Zein protein. Results indicated that hardness of raisins of both varieties was increased due to Zein protein coating and sulphur treatment. The adhesiveness of sulphur treated and Zein coated raisins was reduced in Thompson seedless variety. The raisins of Sonaka and Thompson seedless variety had the least cohesiveness under sulphur, Zein protein coating indicated that both treatments improved durability of and deformation of raisins during post harvest storage. From these results it is concluded that application of sulphur and Zein protein coating on raisins of Sonaka and Thompson seedless is beneficial for maintenance of overall texture of raisins during storage and transport.